Management of public policy in health and user satisfaction of the guasmo sur general hospital in Guayaquil, Ecuador, 2024 - Carreño Calderon, Ricarte Francisco (2024)
This study examines the relationship between the management of public health policies and user satisfaction at the Guasmo Sur General Hospital in Guayaquil, Ecuador, during 2024. Through a quantitative approach and a correlational design, the main factors affecting the perceived quality of health services were identified, including accessibility, infrastructure, communication, and operational efficiency. The results show a significant relationship between governing, enabling and value-adding processes with user satisfaction. In addition, it was evident that the availability of resources, transparency in management and hospital infrastructure are key determinants for a positive experience. This analysis offers practical strategies to optimize the quality of health services, highlighting the need for specific interventions that improve administrative management and user perception.